Machine Learning-Driven Optimization of Biodegradable Polymer Nanocomposites for Improved FDM Printability and Strength - Subramani, Raja; Raviteja, Surakasi; Dwivedi, Jaiprakash Narain; Maddike, Ramamohana Reddy; Venkateswarlu, V.; Kumar, Avvaru Praveen (Journal of Composites and Biodegradable Polymers, 2025)
Biodegradable polymer nanocomposites have emerged as promising sustainable materials for additive manufacturing, especially in Fused Deposition Modeling (FDM). However, their printability and mechanical performance remain highly sensitive to formulation variability and process parameter interactions. Addressing these limitations requires a systematic and predictive approach that integrates materials engineering with advanced data-driven tools. The present work aims to develop a machine learning-driven optimization framework for enhancing the printability and strength of biodegradable polymer nanocomposites used in FDM. A series of PLA-based and PHA-modified nanocomposites reinforced with cellulose nanocrystals (CNC) and nanosilica (SiO₂) were fabricated using a design-of-experiments approach. Key extrusion and printing parameters—including nozzle temperature, bed temperature, infill density, raster angle, and feed rate—were systematically varied to generate a comprehensive experimental dataset. Supervised machine learning models (Random Forest, XGBoost, and Artificial Neural Networks) were trained to predict printability indices and mechanical responses, including tensile strength, layer adhesion, and dimensional accuracy. Among the models evaluated, XGBoost achieved the highest predictive accuracy with an R² of 0.96 for tensile strength and 0.94 for printability. Feature importance analysis revealed that nanofiller loading, nozzle temperature, and infill density were the most influential factors. The optimized formulation identified by the ML framework—PLA/PHA with 1.5 wt% CNC—combined with optimal FDM settings resulted in a 22.8% improvement in tensile strength and a 17.4% increase in printability index compared to baseline samples. These results demonstrate that machine learning offers a powerful pathway for designing next-generation biodegradable nanocomposites and advancing sustainable, high-performance FDM manufacturing.